2020
DOI: 10.1063/5.0002964
|View full text |Cite
|
Sign up to set email alerts
|

A feed-forward measurement scheme for periodic noise suppression in atomic magnetometry

Abstract: We present an unshielded, double-resonance magnetometer in which we have implemented a feedforward measurement scheme in order to suppress periodic magnetic noise arising from, and correlated with, the mains electricity alternating current (AC) line. The technique described here uses a single sensor to track ambient periodic noise and feed forward to suppress it in a subsequent measurement. This feed forward technique has shown significant noise suppression of electrical mains-noise features of up to 22 dB und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Our time-frequency analyses have revealed that FSSSC can remove multi-frequency artifacts [ 12 , 28 ]. Environmental noise appears in empty room recordings of the MEG data recorded without a human participant or a phantom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our time-frequency analyses have revealed that FSSSC can remove multi-frequency artifacts [ 12 , 28 ]. Environmental noise appears in empty room recordings of the MEG data recorded without a human participant or a phantom.…”
Section: Discussionmentioning
confidence: 99%
“…Since the artifacts from the OPM sensors are generated by components within the OPMs (e.g., laser, heater, and vapor), these artifacts are called intrinsic artifacts [ 12 , 13 ]. Although some artifacts appear within restricted frequency bands (e.g., powerline noise at 50 Hz or 60 Hz) and spatial subspaces (e.g., out of the head) [ 12 , 13 ], many artifacts in OPM MEG may dynamically vary [ 13 ]. Consequently, it is essential to develop novel methods to remove artifacts in OPM MEG data.…”
Section: Introductionmentioning
confidence: 99%
“…This paper aims to provide a more general analysis of the behaviour of a Bell-and-Bloom magnetometer when it operates in the presence of a generic time dependent field that is parallel to the static (bias) one. The availability of a more accurate model is of relevance when the output of a magnetometer is used as an error-signal to implement feedback based field-stabilization systems [36][37][38][39][40], as well as when designing feed-forward ones [41] or when evaluating the effects of strong stray fields. The later is of particular relevance for systems operated in unshielded environment [9,42].…”
Section: Introductionmentioning
confidence: 99%
“…Precise current control is a vital tool in many scientific applications. Examples include: driving laser diodes 1 , characterisation of semiconductor devices 2 , high impedance tomography and spectroscopy 3 , and magnetic field manipulation [4][5][6] . Each of these applications differs in requirements, but all of them benefit from stability, low noise, and accuracy.…”
Section: Introductionmentioning
confidence: 99%